La «Gazette d’Épidaure» (1761-1763) et la poétique du périodique médical au XVIIIe siècle - Bénédicte Prot (Diciottesimo Secolo)
The «Gazette d’Épidaure» by the physician Jacques Barbeu-Dubourg articulates the periodical press and the dissemination of knowledge on health in the 18th century. In order to reach and please a wide audience of physicians, scholars and amateurs, the doctor-journalist claims diversity, composes a polyphonic medical gazette, and sometimes uses fictional masks and a comic register. The immediate critics of the gazette address the question of the poetics of the medical periodical. This article thus explores the relationship between press, medicine and literature in Enlightenment France.